Agrarian Relations and the Left Movement in Kerala A Note on Recent Trends - N Krishnaji (ECONOMIC AND POLITICAL WEEKLY, 1979)
The abolition of tenancy is widely believed to be accomplished fact in Kerala. The effective implementation of the law was possible largely due to the organised strength of the left movement in the state and the related fact that land reforms in Kerala were implemented by left-oriented governments. The movement which has developed in Kerala since the abolition of tenancy has three main components : successful struggle for higher wages for agricultural labourers; espousal of the demand for 'fair' prices for farm products; and struggle for land. This paper attempts to understand these recent trends in the left movement in the light of long-term changes that have taken place in agrarian relations.